Bleeding hearts: from passionate activism to violent insurgency in Egypt - Hendawy, Abdallah (Lexington Books, 2022)
"This book explores the wave of violent radicalization in post-2011 Egypt and argues that it is the result of unrelenting tension between aspirations, grievances, emotions, meanings, and societal beliefs. [The author] examines the wave of violence that broke out in Egypt in the aftermath of the 2013 military takeover against the country's first democratically elected president. Abdallah Hendawy sheds light on stories of several political activists who abandoned their commitment to nonviolence and took up arms against the state. Through multiple interviews, ethnographic observations, field work, and qualitative data analysis, Hendawy challenges the dominant theoretical paradigms on radicalization that often attribute this complex phenomenon to ideological or religious beliefs. Hendawy thoroughly examines the tumultuous events that followed the 2013 military takeover and the journey of several radicalized individuals. He demonstrates how and why select Egyptian activists turned to violent tactics in the course of their political engagement."--